2018
DOI: 10.1038/s41593-018-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Myelin remodeling through experience-dependent oligodendrogenesis in the adult somatosensory cortex

Abstract: The generation of oligodendrocytes in the adult CNS provides a means to adapt the properties of circuits to changes in life experience. However, little is known about the dynamics of oligodendrocytes and the extent of myelin remodeling in the mature brain. Using longitudinal in vivo two photon imaging of oligodendrocytes and their progenitors in the mouse cerebral cortex, we show that myelination is an inefficient and extended process, with half of the final complement of oligodendrocytes generated after four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
574
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(628 citation statements)
references
References 47 publications
(97 reference statements)
32
574
2
3
Order By: Relevance
“…Myelination continues throughout adulthood (Hill et al, 2018; Hughes et al, 2018; Young et al, 2013). Therefore, we next characterized 6-month-old CC and found that TFEB cKO mice exhibit thicker myelin sheaths (compare Figure 4F’ to 4F; see also Figure S4K; quantified in Figures 4G–H) and increased myelin wrap numbers (Figures S4I–J).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelination continues throughout adulthood (Hill et al, 2018; Hughes et al, 2018; Young et al, 2013). Therefore, we next characterized 6-month-old CC and found that TFEB cKO mice exhibit thicker myelin sheaths (compare Figure 4F’ to 4F; see also Figure S4K; quantified in Figures 4G–H) and increased myelin wrap numbers (Figures S4I–J).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in the rat cortex, approximately 20–30% of pre-OLs die by postnatal day 21 (P21)(Trapp et al, 1997). Recent in vivo imaging work suggests that OL apoptosis also occurs in the adult rodent brain, where most pre-OLs die prior to committing to myelination (Hill et al, 2018; Hughes et al, 2018). To account for the vulnerability of pre-OLs, a model was proposed hypothesizing that when OPCs differentiate to pre-OLs, they rapidly lose their PDGF receptors that typically promote cell survival, thus becoming sensitized to cell death cues (Barres and Raff, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent in vivo longitudinal two-photon imaging studies showed that, in the murine cortex, OL density continues to increase until two years of age [10], and more than half of the OLs present in middle aged mice are produced during adult life (i.e., after fourmonths of age [9]). The generation of such adult-born OLs is required to maintain proper axonal functions [12], and is involved in the production of new myelin segments [9] and changes of the circuit properties subserving experience-dependent plasticity (i.e., motor skills learning [7,8]). However, in both adult human and rodent CNS, the density, distribution and proliferative rate of NG2 glia seem to be independent of the presence/density of myelinated fibres.…”
Section: Introductionmentioning
confidence: 99%
“…These cells persist in the adult CNS parenchyma, where they comprise about 5% of all CNS cells [2], and can serve as a rapidly responding reservoir for new OLs in case of demyelination [1,3,4]. In intact adult nervous tissue, NG2 glia can also be engaged in proliferation and maturation to sustain a certain degree of oligodendrogenesis [5,6] and myelin plasticity [7][8][9][10][11]. Notably, recent in vivo longitudinal two-photon imaging studies showed that, in the murine cortex, OL density continues to increase until two years of age [10], and more than half of the OLs present in middle aged mice are produced during adult life (i.e., after fourmonths of age [9]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation